2003
DOI: 10.1037/0022-006x.71.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Relations of positive and negative affectivity to anxiety and depression in children: Evidence from a latent variable longitudinal study.

Abstract: The tripartite model of anxiety and depression has been studied with adults; however, support is still emerging with children concerning measurement and relations between positive (PA) and negative (NA) affect and psychopathology. In this longitudinal study of 270 4th- to 11th-grade children (mean age = 12.9 years, SD = 2.23). confirmatory factor analysis supported a 2-factor orthogonal model of children's self-reported affect and revealed that the concurrent relations of NA and PA to anxiety and depression sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
190
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(224 citation statements)
references
References 84 publications
(144 reference statements)
31
190
2
1
Order By: Relevance
“…Three studies using self-report measures have found that the combination of high NE/A and low PE/A is associated with: (1) depressive disorders, and changes over time in depression, and not anxiety, in inpatient youth (Joiner and Lonigan 2000); (2) 4th-through 11th-grade youth changes in depressive symptoms over 7 months (Lonigan et al 2003); and (3) 6th-to 10th-grade adolescents' increases in anhedonic symptoms of depression over a five-month period (Wetter and Hankin 2009). Another longitudinal study that assessed 3-year-old children's temperament with parent report and laboratory and observational measures of NE/A and PE/A found neither NE/A nor PE/A predicted depressive symptoms at age 7, yet the interaction of mother-reported NE/A with PE/A predicted depression at age 10, with high NE/A related to increases in depression for children who were low in PE/A (Dougherty et al 2010).…”
Section: Emotional Reactivity and Affectmentioning
confidence: 99%
“…Three studies using self-report measures have found that the combination of high NE/A and low PE/A is associated with: (1) depressive disorders, and changes over time in depression, and not anxiety, in inpatient youth (Joiner and Lonigan 2000); (2) 4th-through 11th-grade youth changes in depressive symptoms over 7 months (Lonigan et al 2003); and (3) 6th-to 10th-grade adolescents' increases in anhedonic symptoms of depression over a five-month period (Wetter and Hankin 2009). Another longitudinal study that assessed 3-year-old children's temperament with parent report and laboratory and observational measures of NE/A and PE/A found neither NE/A nor PE/A predicted depressive symptoms at age 7, yet the interaction of mother-reported NE/A with PE/A predicted depression at age 10, with high NE/A related to increases in depression for children who were low in PE/A (Dougherty et al 2010).…”
Section: Emotional Reactivity and Affectmentioning
confidence: 99%
“…As predicted, negative affectivity was highly correlated with both depression and anxiety and positive affectivity was negatively correlated with depression. Lonigan et al (2003) evaluated the stability of negative and positive affectivity and its relation to anxiety and depression. Consistent with the hypothesis, negative and positive affectivity were related to anxiety and depression; additionally, the results indicated the stability of positive and negative affectivity across time.…”
Section: Positive and Negative Affectivitymentioning
confidence: 99%
“…The tripartite model posits that high levels of negative affect (NA) are shared by anxiety and depression whereas low levels of positive affect (PA) are presumed to be unique to depression and physiological hyperarousal [PH] unique to anxiety. Evidence suggests that NA and PA represent temperamental factors that act as risk factors for anxiety and mood disorders whereas the temperamental status of PH is less clear [6,7].…”
Section: Introductionmentioning
confidence: 99%